Exploring the major cross-talking edges of competitive endogenous RNA networks in human Chronic and Acute Myeloid Leukemia - Sen, Kamalika; Bhattacharyya, Dhananjay; Sarkar, Arijita; Das, Jyotirmoy; Maji, Nilanjana; Basu, Moitri; Ghosh, Zhumur; Ghosh, Tapash Chandra (Biochimica et biophysica acta. General subjects, 2018)
Human Chronic and Acute Myeloid Leukemia are myeloproliferative disorders in myeloid lineage of blood cells characterized by accumulation of aberrant white blood cells. In cancer, the anomalous transcriptome includes deregulated expression of non-coding RNAs in conjunction with protein-coding mRNAs in human genome. The coding or non-coding RNA transcripts harboring miRNA-binding sites can converse with and regulate each other by explicitly contending for a limited pool of shared miRNAs and act as competitive endogenous RNAs (ceRNAs). An unifying hypothesis attributing ‘modulation of expression of transcripts’ in this fashion had been defined as ‘competitive endogenous RNA hypothesis’. Network built with ceRNAs evidently offers a platform to elucidate complex regulatory interactions at post-transcriptional level in human cancers. Contemplating cancers of human myeloid lineage we constructed ceRNA networks for CML and AML coding and non-coding repertoire utilizing patient sample data. Through functional enrichment analysis we selected the significant functional modules for transcripts being differentially expressed in Blastic phases of each cancer types with respect to Normal. After retrieving free energy of binding and duplex formation of shared miRNAs on ceRNAs, we performed statistical averaging of energy values over the ensemble of populations considering cellular system as in canonical (Iso-thermal) situation. We aimed to shed light on ‘Sibling Rivalry’ in ceRNA partners from the perspective of statistical thermodynamics, identified major cross-talking tracks and ceRNAs influencing transcripts concerned in myeloid cancer systems. Insights into ceRNA-regulation will shed light on progression and prognosis of human Chronic and Acute Myeloid Leukemia. •ceRNA network (ceRNET) formed on CML and AML patient sample data.•Functional Enrichment analysis for ceRNETs of differentially expressed transcripts.•Thermodynamic favorability, site accessibility of miRNA-mRNA duplex was analyzed.•Significant cross-talking neighbors in ceRNETs of myeloid leukemia were identified.